2021
DOI: 10.1055/a-1333-4099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 Pandemic in German Trauma Centres and Geriatric Trauma Centres DGU

Abstract: Background The COVID 19 pandemic is a major challenge to all social systems, particularly the healthcare system. Within an international study, German Trauma Centres DGU and Geriatric Trauma Centres DGU have been questioned about their situation. Method The questionnaire was translated from English into German and sent to all contacts. The evaluation was performed descriptively. Results 71 of 692 centres participated in this study. Government instructions to avoid elective treatments have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
0
9
0
8
Order By: Relevance
“…It is commonly agreed that fractures of the proximal femur should be treated within 24 hours. In the context of COVID-19, the logistical challenges for hospitals in guaranteeing immediate surgery are considerable, 13,14 and as a matter of current debate, the influence of the best time to surgery remains unknown. 15e18 Our data showed no difference in time to surgery, and hospitals were able to provide surgery within 24 hours for most patients (77.9% and 74%), independently of whether they had tested positive or negative (P ¼ .436).…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly agreed that fractures of the proximal femur should be treated within 24 hours. In the context of COVID-19, the logistical challenges for hospitals in guaranteeing immediate surgery are considerable, 13,14 and as a matter of current debate, the influence of the best time to surgery remains unknown. 15e18 Our data showed no difference in time to surgery, and hospitals were able to provide surgery within 24 hours for most patients (77.9% and 74%), independently of whether they had tested positive or negative (P ¼ .436).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study by Kuhlen et al, which analyzed the data of the optional external quality program IQM found a decrease of femoral neck fractures of nearly 24% and of trochanteric femur fractures of nearly 19% [11]. This is also supported by the results of Schoeneberg et al They conducted an online survey of all registered German Trauma Centers and Geriatric Trauma Centers [12]. These results do not only represent results from maximum care hospitals and Level 1 hospitals, but from all levels of health care in Germany.…”
Section: Discussionmentioning
confidence: 90%
“…Diese Schritte führten u. a. zu einem immensen Rückgang der Operationen im Bereich der Unfallchirurgie/Orthopädie [ 5 , 8 , 14 , 16 , 18 , 23 ]. Einzelne Arbeiten zeigen jedoch bereits, dass nicht nur die Zahl der elektiven Operationen zurückgegangen ist, sondern auch die konservativen Therapien von Frakturen während der Pandemiezeit zugenommen haben [ 18 ]. Weiterhin beschreiben mehrere Autoren nach Auswertung von medizinischen Fallzahlen in deutschen Kliniken einen Rückgang verschiedener Frakturinzidenzen [ 11 , 18 ].…”
Section: Introductionunclassified